2012
DOI: 10.1002/ajh.23137
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic screening of the main opiate‐related polymorphisms in a cohort of 139 sickle cell disease patients

Abstract: 10. Ko M, Huang Y, Jankowska AM, et al. Impaired hydroxylation of 5-methylcytosine in myeloid cancers with mutant TET2. Much of sickle cell disease (SCD) morbidity is due to recurrent painful crises mainly treated by codeine and morphine. However, surprisingly, there are no genotypic data that relate to the frequency of the main opiate-related SNPs in SCD populations [4]. One may argue that the allelic frequencies for African-Americans (AA) are known and that, since SCD patients are mostly of AA origins, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…With respect to the percentages of poor metabolizers and ultrarapid metabolizers, our findings are consistent with other CYP2D6 genotype analyses in African American patients with or without SCD and differ from the distribution of CYP2D6 phenotypes in individuals of European ancestry. [45][46][47][48] African American patients are more likely to be ultra-rapid metabolizers and less likely to be poor metabolizers compared with individuals of European ancestry. In our cohort, 53 patients with SCD (9% of patients with a known CYP2D6 genotype) have a high-risk CYP2D6 result (44 ultra-rapid metabolizers or possible ultra-rapid metabolizers and 9 poor metabolizers).…”
Section: Figurementioning
confidence: 99%
“…With respect to the percentages of poor metabolizers and ultrarapid metabolizers, our findings are consistent with other CYP2D6 genotype analyses in African American patients with or without SCD and differ from the distribution of CYP2D6 phenotypes in individuals of European ancestry. [45][46][47][48] African American patients are more likely to be ultra-rapid metabolizers and less likely to be poor metabolizers compared with individuals of European ancestry. In our cohort, 53 patients with SCD (9% of patients with a known CYP2D6 genotype) have a high-risk CYP2D6 result (44 ultra-rapid metabolizers or possible ultra-rapid metabolizers and 9 poor metabolizers).…”
Section: Figurementioning
confidence: 99%
“…The survey includes genotype and allele frequency data for genes including OPRM1 (rs1799971) and ABCB1 (rs1045642) in an SCD cohort [24]. We found no differences between our study population and their two cohorts for these two SNPs for either genotype or allele frequencies.…”
Section: Resultsmentioning
confidence: 62%
“…A previous study reported major opiate-related polymorphisms in an SCD cohort [24]. The survey includes genotype and allele frequency data for genes including OPRM1 (rs1799971) and ABCB1 (rs1045642) in an SCD cohort [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported a similar higher promoter activity of haplotype II over haplotype I in the context of much shorter promoter regions; however, the functionality of this SNP was not verified by mutagenesis in these studies (Duguay et al, 2004;Nakamura et al, 2008). To further support the importance of this SNP, recent studies have shown that the production of acylmycophenolic acid-glucuronide was significantly higher in AA-and GA-human liver microsomes compared with GG-human liver microsomes (Djebli et al, 2007) and that GG and GA genotypes were associated with lower morphine glucuronide/morphine AUC (area under the concentration-time curve) ratios compared with the ratios of AA genotypes in patients with sickle cell disease treated with morphine (Darbari et al, 2008;Joly et al, 2012). Nakamura et al (2008) showed binding of transcription factors to the UGT2B7 promoter region covering SNP -900A.G by electrophoretic mobility shift assays; however, the identity of the transcription factor(s) involved was not defined in this study.…”
Section: Discussionmentioning
confidence: 99%